Philosophia from Dialectic to Dying Before Death: Traces of Plato’s Spirit in the Encounters Between the Falāsifa, Mutakallimūn, and Sūfiyya - Yunus Alsagoff, Fadhil (AUC Knowledge Fountain, 2026)
This thesis offers a fresh approach to the question “What is philosophy?” by reconsidering Plato’s vision of philosophiaand seeking its traces in the encounters between the Falāsifa, the Mutakallimūn, and the Sūfiyya of the classical Muslim world. I argue that Plato’s true legacy lies in a vision of philosophia as dialectical inquiry that ultimately leads – due to the inextricable limitations of propositional language – to aporia and what he called “practicing for dying and death.” I then argue that this vision of philosophia finds resonance in the classical Muslim world in the embodied encounters between the rationalism of the falāsifa and mutakallimūn - who saw Plato as a rationalist philosopher – on the one hand, and the mysticism of the Sufis – who saw Plato as a divine sage – on the other. In considering such encounters as expressions of Plato’s vision of philosophia, I seek to show that the relation between rational inquiry and mysticism – and thus, the relation between what I call “the two faces of the Muslim Plato” – is one of neighbourhood and not violation. In doing so, I challenge dominant Western narratives that dichotomize “Occidental” and “Oriental” approaches to wisdom, separating the philosopher from the sage, and restate a vision of philosophy unconfined by cultural or linguistic boundaries—a shared human striving after wisdom that culminates in dying to the self in pursuit of truth.